Limb salvage in diabetic patients with no-option critical limb ischemia: outcomes of a specialized center experience. Issue 1 (1st January 2019) - Dalla Paola, Luca; Cimaglia, Paolo; Carone, Anna; Scavone, Giuseppe; Boscarino, Giulio; Bernucci, Davide; Sbarzaglia, Paolo; Censi, Stefano; Ferrari, Roberto; Campo, Gianluca
ABSTRACT: Objective : To describe the characteristics, the management and the outcome of a consecutive series of patients with diabetic foot lesions (DF) and no-option critical limb ischemia (CLI) treated with a multidimensional, interdisciplinary approach in a dedicated center. Research Design and Methods : The prospective database of the Diabetic Foot Unit of the Maria Cecilia Hospital (Cotignola, Italy) collects medical history, risk factors, chemistry values, angiographic data, characteristic of foot lesions, medical and surgical therapies of all patients admitted with a diagnosis of DF and CLI. All patients were followed-up for at least 1 year and/or total recovery. The primary endpoint was 1-year amputation-free survival (AFS), secondary endpoints were limb salvage and survival. Results : Between October 2014 and October 2017, 1024 patients with DF and CLI were admitted to the center. Eighty-four of them (8.2%) fulfilled the criteria for no-option CLI. At 1 year, AFS, limb salvage, and survival rates were 34%, 34%, and 83%, respectively. Lesions located proximal to the Lisfranc joint were associated with major amputation (HR 2.1 [1.2–3.6]). One-year survival of patients treated with minor procedures was significantly higher compared to patients treated with major amputation (96% vs 76%, log-rank p = 0.019). Major amputation was independently associated with mortality (HR 7.83 [1.02–59.89]). Conclusions : The application of dedicated and standardized strategies permitted limb salvage in one-third of patients with no-option CLI. Patients with stable lesions limited to the forefoot and without ischaemic pain had a greater probability to successfully receive conservative treatments. Limb salvage was associated with subsequent higher one-year survival.